"Are they becoming more reflective and/or efficacious?" A conceptual model mapping how teachers' self-efficacy beliefs might grow. Issue 1 (2nd January 2016) - Wyatt, Mark
Abstract : Conceptual models can fulfil important educative roles, particularly in fields where there are few such models and where constructs are confused, as in research into teachers' self-efficacy beliefs. In this area, one model developed in the late twentieth century subsequently became dominant, but seems flawed. This article addresses criticisms of it and then presents an alternative, this centred on a reflective learning cycle. The new model emerged from a qualitative longitudinal multi-case study of English language teachers developing practical knowledge and self-efficacy beliefs while on an in-service teacher education programme in Oman. Its relevance for other contexts is considered.